2012
DOI: 10.2187/bss.26.32
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of PsPINs and PsAUX1 cDNAs Encoding Putative Auxin Efflux and Influx Carriers and/or Facilitators, Respectively, from Etiolated Epicotyls of an Agravitropic Pea (Pisum sativum L.) Mutant, ageotropum

Abstract: cDNAs containing the open reading frames of a putative auxin influx carrier and/or facilitator, PsAUX1 (Accession No. AB488680), and putative auxin efflux carriers and/or facilitators, PsPIN1, PsPIN2 and PsPIN3 (Accession No. AB488679, AB488681 and AB488678, respectively) from etiolated epicotyls of an agravitropic pea mutant, ageotropum, have been isolated. In PsPIN1 and PsPIN2, a few deduced amino acids were different between ageotropum and Alaska showing a normal gravitropic response. No insertion and delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Auxin polar transport was determined according to the method reported previously (Oka et al, 1995;Ueda et al, 1999Ueda et al, , 2000Ueda et al, , 2012Ueda et al, , 2013Hoshino et al, 2007) , American Radiolabeled Chemicals Inc., St. Louis, Mo.) was prepared in 1.5 ml Eppendorf tubes, and was incorporated into the apical or the basal side of the segments in the tube.…”
Section: Determinations Of Auxin Polar Transportmentioning
confidence: 99%
See 3 more Smart Citations
“…Auxin polar transport was determined according to the method reported previously (Oka et al, 1995;Ueda et al, 1999Ueda et al, , 2000Ueda et al, , 2012Ueda et al, , 2013Hoshino et al, 2007) , American Radiolabeled Chemicals Inc., St. Louis, Mo.) was prepared in 1.5 ml Eppendorf tubes, and was incorporated into the apical or the basal side of the segments in the tube.…”
Section: Determinations Of Auxin Polar Transportmentioning
confidence: 99%
“…After the designated incubation period, the radioactivity on the opposite sides (1 to 2 mm) of the segment was directly determined using a liquid scintillation counter and auxin polar transport was shown by the radioactivity. This method has been considered to be suitable for the determination of auxin polar transport (Okada et al 1991;Oka et al 1995Oka et al , 1998Oka et al , 1999Ueda et al, 2012). Since radioactivities transported from basal to apical side of the segments were extremely small (Okada et al 1991;Oka et al 1995Oka et al , 1998Oka et al , 1999Ueda et al, 2012), only [ 14 C]IAA from the apical side of the segments was shown as a result.…”
Section: Determinations Of Auxin Polar Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we also succeeded in isolating novel cDNAs containing the complete open reading flame encoding putative auxin efflux carrier proteins, PsPIN1 (Chawla & DeMason ; Ueda et al . ), PsPIN2 (Hoshino et al . ; Ueda et al .…”
Section: Polar Auxin Transport Related To Automorphosis In Plantsmentioning
confidence: 99%